Quality of refrigerated Assaf and Blackbelly ram semen - Castro Bedriñana, Jorge Isaac (2017)
Chilled semen quality of Assaf and Blackbelly rams used in artificial insemination and raised in the central coast of Peru were compared. Semen was collected with an artificial vagina and diluted with Tris-fructose-egg yolk. The individual progressive motility, the membrane integrity by the hypoosmotic text (HOST), and sperm concentration in the Neubauer chamber were determined after two hours of refrigeration. The percentage values were previously transformed into ArcSen %. The Student «t» test for independent means differences between breeds was performed. Progressive individual motility was 82.36 ± 6.66 and 83.30 ± 4.92% (p>0.05) and the mass motility was 4.28 ± 0.45 and 4.06 ± 0.33 (p<0.05) for the Assaf and for Blackbelly rams, respectively. The integrity of the spermatic membrane was 83.50 ± 2.77% for Assaf and 82.56 ± 3.78% for Blackbelly (p<0.05). Sperm concentration and percentages of live and abnormal spermatozoa were similar in both breeds.